(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2018)
Antennas with given radiation pattern may be arranged in a pattern (line, circle, plane etc.) to yield a different radiation pattern. An antenna array is a configuration of multiple antennas (elements) arranged to achieve the given radiation pattern. These arrays are classified as linear array, circular array, planar array etc. based on placement or an arrangement of these multiple elements in a specific geometrical shape. There are multiple design issues of the antenna array are available in the form of different variables such as, shape of the array, element spacing between array elements, excitation amplitude of individual array element, excitation phase of the individual array element, patterns of array elements etc.